CIMPACT‐NOW update 7: advancing the molecular classification of ependymal tumors. (23rd June 2020) - Ellison, David W.; Aldape, Kenneth D.; Capper, David; Fouladi, Maryam; Gilbert, Mark R.; Gilbertson, Richard J.; Hawkins, Cynthia; Merchant, Thomas E.; Pajtler, Kristian; Venneti, Sriram; Louis, David N.
Abstract: Advances in our understanding of the biological basis and molecular characteristics of ependymal tumors since the latest iteration of the World Health Organization (WHO) classification of CNS tumors (2016) have prompted the cIMPACT‐NOW group to recommend a new classification. Separation of ependymal tumors by anatomic site is an important principle of the new classification and was prompted by methylome profiling data to indicate that molecular groups of ependymal tumors in the posterior fossa and supratentorial and spinal compartments are distinct. Common recurrent genetic or epigenetic alterations found in tumors belonging to the main molecular groups have been used to define tumor types at intracranial sites; C11orf95 and YAP1 fusion genes for supratentorial tumors and two types of posterior fossa ependymoma defined by methylation group, PFA and PFB. A recently described type of aggressive spinal ependymoma with MYCN amplification has also been included. Myxopapillary ependymoma and subependymoma have been retained as histopathologically defined tumor types, but the classification has dropped the distinction between classic and anaplastic ependymoma. While the cIMPACT‐NOW group considered that data to inform assignment of grade to molecularly defined ependymomas are insufficiently mature, it recommends assigning WHO grade 2 to myxopapillary ependymoma and allows grade 2 or grade 3 to be assigned to ependymomas not defined by molecular status.